2017
DOI: 10.1093/jac/dkx005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and impact of Clostridium difficile recurrence on haematology patients

Abstract: Haematology patients exhibit a higher rate of rCDI than general hospitalized patients. Utilization of this multivariable model to guide index CDI therapy at index may help to decrease the rCDI and prevent delays or interruptions in chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
3
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 35 publications
5
13
3
2
Order By: Relevance
“…Patients under antibiotic treatment were at a higher risk for acquiring C. difficile (RR: 3.81, OR: 5.29, p <0.05). These results are in agreement with those of Gianni et al ( 27 ) who reported that previous antibiotic use is the predominant risk factor for C. difficile acquisition, with relative risk of 5.9. Females were at a significantly higher risk for acquiring C. difficile than males (RR: 1.5, OR: 1.22, p < 0.05) which agreed with what was reported by Timothy et al ( 28 ) (OR: 1.50, p: < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Patients under antibiotic treatment were at a higher risk for acquiring C. difficile (RR: 3.81, OR: 5.29, p <0.05). These results are in agreement with those of Gianni et al ( 27 ) who reported that previous antibiotic use is the predominant risk factor for C. difficile acquisition, with relative risk of 5.9. Females were at a significantly higher risk for acquiring C. difficile than males (RR: 1.5, OR: 1.22, p < 0.05) which agreed with what was reported by Timothy et al ( 28 ) (OR: 1.50, p: < 0.05).…”
Section: Discussionsupporting
confidence: 93%
“…Indeed, a large Spanish study suggests a higher increase of CDI in hospitalized female patients compared to men of the same age (Esteban-Vasallo et al, 2016). However, in the allo-HSCT cohort, the distribution of sex was similar in both CDI and NCDI groups; in agreement, several studies of hematological patients suggested no sex differences (Alonso et al, 2013;Bilgrami et al, 1999;Scappaticci et al, 2017;Trifilio et al, 2013). Therefore, the statistical female overrepresentation might as well be an epiphenomenon in our study.…”
Section: Discussionsupporting
confidence: 85%
“…Apesar dos esforços para prevenir a CDI nos últimos anos, sua incidência vem aumentando no mundo (Raza et al, 2010), com uma variabilidade nas diferentes regiões, ressaltando a importância das investigações regionais. No leste da China, Fang et al, (2014) encontraram uma prevalência de 20,5% de CDI em três hospitais oncológicos; na Espanha esse percentual foi de 17,3% (Garzotto et al, 2015) e nos EUA, a incidência de CDI foi de aproximadamente 7-14% em adultos com câncer (Scappaticci et al, 2017).…”
Section: Discussionunclassified